A Review and Meta-Analysis of the Studies Conducted on the Impact of Micropollutants on the Aggressive Behaviors of Some Crustaceans - Patrick, Rosemary; Egbuatu , Maureen (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The aquatic environment is constantly polluted by point and non-point sources of contaminants, endangering animals. For example, micropollutants and heavy metals have been demonstrated to influence the physiology and behavior of crustaceans. Some research has reported that the aggressive behavior of crustaceans tends to change as an early warning sign of environmental contamination. A meta-analysis of the effects of micropollutants and heavy metals on crustaceans’ behavior. The results show that, for all investigated pollutant effects on fight duration across 18 datasets, the SMD range was -1.26 to 0.64 with a heterogeneity (Q) of 267.11 (p < 0.01), indicating high variability among studies. The publication bias p-value was 0.27, suggesting no significant publication bias for this endpoint. Specifically, for micropollutants affecting fight duration in 11 datasets, the SMD ranged from -1.41 to 1.02, with a heterogeneity (Q) of 182.82 (p < 0.01), again showing high variability. The publication bias p-value was 0.76, indicating no significant publication bias. Regarding the effects of all investigated pollutants on the number of fights in 10 datasets, the SMD ranged from -3.32 to -1.01, showing a statistically significant negative impact on aggressive interactions. The heterogeneity (Q) was 83.37 (p < 0.01), and the publication bias p-value was <0.01, indicating a significant publication bias for this endpoint. For micropollutants specifically affecting the number of fights in 7 datasets, the SMD ranged from -3.75 to -0.41, with a heterogeneity (Q) of 77.32 (p < 0.01) and a publication bias p-value of <0.01, again indicating a significant publication bias. When the size effect values and standard mean differences in confidence intervals of the different investigations were considered, the review revealed a high heterogeneity of published results and a tendency to find publication bias. The analysis concluded that aggressive behavior as an early warning sign for environmental contamination should be performed with caution because the levels required to trigger a response in some species are frequently insignificant regarding environmental relevance.